2011
DOI: 10.1007/s11357-011-9281-x
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle contractile function and neuromuscular performance in Zmpste24 −/− mice, a murine model of human progeria

Abstract: Human progeroid syndromes and premature aging mouse models present as segmental, accelerated aging because some tissues and not others are affected. Skeletal muscle is detrimentally changed by normal aging but whether it is an affected tissue in progeria has not been resolved. We hypothesized that mice which mimic Hutchinson-Gilford progeria syndrome would exhibit age-related alterations of skeletal muscle. Zmpste24 −/− and Zmpste24 +/+ littermates were assessed for skeletal muscle functions, histo-morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 48 publications
(72 reference statements)
0
35
0
Order By: Relevance
“…However, PS patients commonly have decreased NMJ performance[27], defects in the enteric nervous system[28], low-frequency conductive hearing loss, and peripheral neuropathy[29]. Thus, synaptic dysfunction in PS patients cannot be completely ruled out.…”
Section: Resultsmentioning
confidence: 99%
“…However, PS patients commonly have decreased NMJ performance[27], defects in the enteric nervous system[28], low-frequency conductive hearing loss, and peripheral neuropathy[29]. Thus, synaptic dysfunction in PS patients cannot be completely ruled out.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have reported that mutation of lamin A, a major component of the nuclear envelope, has an adverse effect on skeletal muscle function and myoblast differentiation [7,9,11-14,34]; however, no studies examined earlier muscle stem/progenitor cells residing in muscle tissue. Because degenerative changes associated with progeroid syndromes may have a strong impact on stem cells, we hypothesized that the dysfunction of muscle stems cells in Zmpste24 -/- progeroid mice may contribute to the loss of the cells' ability to regenerate skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…By knocking out Zmpste24 , prelamin A accumulates on the cell nuclear envelope, resulting in cellular blebbing [9,10]. The Zmpste24 -/- mice display accelerated aging, loss of weight, spontaneous bone fracture, cardiomyopathy, muscular dystrophy, muscle atrophy, and muscle weakness [6,7,9,11]. A recent study provides evidence that the skeletal muscles of Zmpste24 -/- mice exhibit impaired muscle contraction and neuromuscular performance [11].…”
Section: Introductionmentioning
confidence: 99%
“…For histology, muscles were embedded in OCT. 10 μm sections were evaluated by hematoxylin and eosin (H&E) staining, NADH reactivity, and myosin heavy chain expression as described (Greising et al, 2012). …”
Section: Methodsmentioning
confidence: 99%